2015
DOI: 10.1007/s12010-015-1712-1
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant–Amino Acid and Surfactant–Surfactant Interactions in Aqueous Medium: a Review

Abstract: An overview of surfactant-amino acid interactions mainly in aqueous medium has been discussed. Main emphasis has been on the solution thermodynamics and solute-solvent interactions. Almost all available data on the topic has been presented in a lucid and simple way. Conventional surfactants have been discussed as amphiphiles forming micelles and amino acids as additives and their effect on the various physicochemical properties of these conventional surfactants. Surfactant-surfactant interactions in aqueous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 177 publications
(182 reference statements)
0
25
0
1
Order By: Relevance
“…The study of the interactions between surfactants, both synthetic and microbial (biosurfactants), with proteins is of great interest in various biotechnology fields and industries such as food, cosmetics, pharmaceutical, biomedical, and environmental (Lee et al 2011;Otzen 2011;Tucker et al 2014;Malik 2015). In the biomedical industry, protein-surfactant systems are used for the production of hydrogels (Afinjuomo et al 2019;Castelli et al 2008).…”
Section: Surfactant-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the interactions between surfactants, both synthetic and microbial (biosurfactants), with proteins is of great interest in various biotechnology fields and industries such as food, cosmetics, pharmaceutical, biomedical, and environmental (Lee et al 2011;Otzen 2011;Tucker et al 2014;Malik 2015). In the biomedical industry, protein-surfactant systems are used for the production of hydrogels (Afinjuomo et al 2019;Castelli et al 2008).…”
Section: Surfactant-protein Interactionsmentioning
confidence: 99%
“…The main physical parameters that have an effect on the surfactant-protein interactions are: (a) the surfactant concentration; (b) the chemical nature of surfactant (ionic or non-ionic surfactants); and (c) the secondary structure of the protein (a-helix and bsheets) (Díaz et al 2003;Malik 2015).…”
Section: Surfactant-protein Interactionsmentioning
confidence: 99%
“…As shown in Table 3, it is found that TH3 has signicant advantages in shortening the induction time, which may be the coordination of multiple unit promoters aer compounding. 43 To further understand the effects of additives on the characteristics of hydrate formation, subsequent work should be conducted with other experimental conditions.…”
Section: Effect Of Dosage On the Formation Characteristics Of Methanementioning
confidence: 99%
“…[29][30][31][32] For the rational design of such tailor-made complexes, deeper insight into the major factors governing the of the interaction between amino acids (AAs) and surfactants is needed. Extensive knowledge has been gathered in the field of the binding of conventional surfactants to AAs, [33][34][35][36][37][38][39][40][41][42][43] but the effect of AAs on the self-assembly of 1-alkyl-3-methylimidazolium type of amphiphiles has not been studied in detail. In this work, we study how the presence of L-alanine (L-Ala), L-phenylalanine (L-Phe), and L-tryptophan (L-Trp) AAs modifies the micellization properties of 1-tetradecyl-3methylimidazolium bromide [C 14 mim][Br] in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%